2021
DOI: 10.21203/rs.3.rs-562573/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the Antibacterial Effects and Mechanism of Plantaricin 149 from Lactobacillus Plantarum NRIC 149 on the Peri-Implantitis Pathogens

Abstract: Peri-implantitis is a common reversible disease after tooth implantation, caused by a variety of pathogenic microorganisms. Based on non-surgical or surgical treatment principles, supplementation by local or systemic drugs might enhance treatment efficacy. Porphyromonas gingivalis (Pg) (ATCC 33277) and Prevotella intermedius (Pi) (ATCC 25611) were used as test strains. The effects of Pln 149 on the biofilm formation and growth of four periodontal pathogens were evaluated by RT-PCR, fluorescence microscopy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Recent research has shown that the bacterial population in the biofilm works like a 'bacterial brain, ' which means bacteria could communicate with each other through ion channel-mediated electric signals [33]. Our previous study showed that Pln 149 could inhibit ion channels [29], and in our current experiment, Pln 149 showed strong anti-biofilm effects on root canal biofilms. With no cytotoxicity to human dental pulp stem cells, Pln 149 offers promising applications as an irrigation solution and disinfection medicament in root canals.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Recent research has shown that the bacterial population in the biofilm works like a 'bacterial brain, ' which means bacteria could communicate with each other through ion channel-mediated electric signals [33]. Our previous study showed that Pln 149 could inhibit ion channels [29], and in our current experiment, Pln 149 showed strong anti-biofilm effects on root canal biofilms. With no cytotoxicity to human dental pulp stem cells, Pln 149 offers promising applications as an irrigation solution and disinfection medicament in root canals.…”
Section: Discussionsupporting
confidence: 51%
“…They are almost found only in infected root canals, with a high detection rate, and are considered to be the core bacteria in the infected root canal. Our previous research showed that Pln 149 exhibited strong antibacterial activity against P. gingivalis, indicating its potential value in root canal irrigation [29].…”
Section: Discussionmentioning
confidence: 97%